(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Anxiety and Examination stress among college students has been a topic of interest for many years. College students experience high stress due to various reasons such as lack of preparation, style of their study and lack of needed information. When stress is perceived negatively or becomes excessive, it leads to anxiety before and during examinations and ultimately affects their academic achievement. The present study was conducted to know the examinations stress felt by college students under Arts, Science and Commerce stream of education. Further comparison was done to find out the level of stress felt by college students enrolled in under graduate and post graduate programmers. The sample consisted of 90 college students drawn using stratified random sampling method from two girl’s colleges. A questionnaire was developed by the researcher to access examination stress and anxiety among college students. The result shows correlation between examination stress and anxiety of college students. On comparing the stress and anxiety among students of different stream, the students of Arts was found having highest stress and anxiety during examination followed by commerce students. There was no significant difference found in the stress and anxiety level of undergraduate and postgraduate students. Key Words: Examination Stress, Anxiety, College students, Arts, Science, Commerce